Permainan Simulasi Proses Bisnis Sebagai Sarana Pembelajaran Proses Bisnis pada Perusahaan Ritel - Joella Joella; Yulia Yulia; Andreas Handojo (Jurnal Infra, 2021)
Game-based Learning becomes one of the most developed learning methods in this 21st century. Game-based Learning is a good learning method because it can create a virtual world where players can simulate real world problem solving. Business process is a series of interrelated activities to achieve certain business goals which are executed sequentially or parallel, both inside and outside the company. The complexity of business processes causes the learning process to be less than optimal if only in the form of theoretical exposure. Practices are needed so that students can hone their business process management skills, but if they practice in the real world, of course it will be very high risk. Therefore, this research develops business process simulation game to facilitate students in practicing their business process management skill. The author analyzed the existing business process simulation games, determined the game system design, developed the game, tested the game, and distribute questionnaires to users. Based on the results of testing and implementing the system that has been done, the game developed in this research give a positive impact on users. The features in the game are running well and as expected. The game provides benefits to users, both teachers and students, so this game is suitable for being used as retail companies’ business process learning tool.